Lean value marketing programs - P F Maxson (Kansas Agricultural Experiment Station Research Reports, 1986)
Recent promotion of the National Pork Producers Lean Guide to Pork Value has focused attention on providing pork producers with an economic incentive to raise lean, meaty hogs. The packing industry version of this value-based idea is generally termed a grade and yield program. While each individual packing plant may have its own grade and yield program, several factors need to be considered when marketing hogs grade and yield, regardless of the packing plant. The preferred weight range for a packing plants grade and yield program must be known. Packing plants available to Kansas usually range from 210-240 lb or from 220-250 lb. If your hogs fall below or above the preferred weight range, price discounts will begin. Generally, the farther a pig is outside the preferred weight range, the greater the discount.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Lean value; Marketing programs